A STUDY OF AL-QUR'AN TOWARDS ENVIRONMENTAL ISSUES OF BUGINESE ELONG-ELONG (ECOCRITICAL APPROACH) - Nahdhiyah, Nahdhiyah; Junaid, Syahruni (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
This research aims to analyze environmental issues in Buginese elong-elong in terms of form and the relationship between humans, nature and God by using ecocritical theory. This research used qualitative approach to get an overview of integration with the interpretation of the Qur'an in Buginese elong-elong. This research used some instruments such as: documentation, questionnaire recording and guideline of focus group discussion (FGD). This research used content analysis technique with Miles and Hubberman theories in analyzing data. There are three steps in analyzing data namely data reduction, data display, and drawing conclusion after verification. Furthermore, the researchers got that nature element is implicitly contained in Buginese elong-elong. Ecocentric and theocentric are most forms occurred as the relationship between humans and nature. Keywords: Ecocritic; Elong-elong; buginese; Mursery Rhyme ستخلص البحثتهدف هذه المقالة إلى تحليل القضايا البيئية فى الغناء البوغيسيي (elong-elong ugi) منن حيث العلاقة بين الإنسان والطبيعة والله باستخدام النظرية ekokritik ثم يتم استخدام نهج نوعي للحصول على صورة تكامل معرفة التفسير القرآني لبوجيس الغناء البوغيسي. أما الأدوات المستخدمة فتكون من الوثائق وتسجيل الاستبيان ومناقشة مجموعة التركيز التوجيهية (FGD). تحليل محتوى باستخدام تقنية Miles and Huberman المستخدمة في تحليل البيانات. هناك ثلاث مراحل لتحليل البيانات وهي تقليل البيانات ، عرض البيانات ، استنتاجات. تم اتتحقق الباحث ان فيالغناء عناصر العلم موجودة في الغناء البوغسيي اشاريا . ، الباحثان تجدان ان اكثر ما وجد فى العلاقة البشرية والطبيعية هي ايكوكريتق (ekosentris) و تبوسنتري (theosentris) . الكلمات الرءيسية : الغناء البوغسي، ايكوكريتق- ، غناء مقدمة للنوم ABSTRAK Penelitian ini bertujuan untuk menganalisis isu-isu lingkungan pada elong-elong Bugis dalam hal wujud dan hubungan antara manusia, alam dan Tuhan dengan menggunakan teori ekokritik. Penelitian ini menggunakan pendekatan kualitatif untuk mendapatkan gambaran bentuk integrasi ilmu tafsir Al Qur’an dalam elong-elong Bugis. Penelitian ini menggunakan beberapa instrumen anatara lain: dokumentasi, pencatatan angket dan guideline focus group discussion (FGD). Penelitian ini menggunakan teknik Content Analysis dengan teori Miles dan Hubberman dalam analisis data. Ada tiga tahap analisis data yaitu: reduksi data, penyajian data dan kesimpulan setelah diverifikasi. Selanjutnya, peneliti mendapatkan bahwa unsur alam terkandung secara tersirat dalam elong-elong Bugis. Ekosentris dan teosentris adalah bentuk yang paling banyak muncul terkait hubungan manusia dan alam.